Timber beams with openings: Laboratory testing and nonlocal finite element modelling. (15th October 2021) - Karimi-Nobandegani, Amir; Valipour, Hamid
Highlights: Behaviour of LVL and glulam timber beams with holes are studied. Results of laboratory tests on LVL and glulam beams with holes are presented. Finite element (FE) modelling of the timber beams with holes are reported. Application of a nonlocal continuum damage law for modelling timber is discussed. Effect of localisation limiters on FE analysis of beams with holes is demonstrated. Abstract: Introducing openings in joists of flooring systems is usually necessary to pass through building services without increasing the floor-to-floor height. The openings reduce the stiffness and limits the ultimate load-carrying capacity of the timber beams by promoting tensile stresses perpendicular to the grain and longitudinal splitting shear stresses. Furthermore, quasi-brittle failure of the timber in shear and tension (promoted by openings) leads to localisation of strain, spurious numerical sensitivities and ultimately poor or erroneous damage initiation and failure load predicted by finite element (FE) models. In this paper, a nonlocal continuum damage model is proposed and implemented to alleviate the FE mesh dependency and strain localisation problems in failure analysis of the timber beams with openings. Benchmark experimental results obtained from bending test on Laminated Veneer Lumber (LVL) and Glued Laminated Timber (GLT or glulam) beams with openings are briefly presented and then accuracy of the implemented nonlocal FE model is validated against the benchmark test results and experimental data available in the literature. It is demonstrated that the proposed nonlocal model can effectively resolve the spurious mesh sensitivity and accurately capture the failure modes and peak load-carrying capacity of timber beams with openings.